Eglerisine, a Novel Sesquiterpenoid Tropolone from Dulacia egleri with Antiproliferative Effect against an Acute Myeloid Leukemia Lineage - R. de Novais, Leice M.; Ferreira, Luiz F.; de Sousa, Paulo T., Jr.; Ribeiro, Tereza A. N.; Jacinto, Marcos J.; dos Santos, Carlos H. C.; de Carvalho, Mário G.; Torquato, Heron F. V.; Paredes-Gamero, Edgar J.; Silva, Virgínia C. P. (Planta Medica, 2020)
Chemical investigation of the stems of Dulacia egleri resulted in the isolation of eglerisine (1), a compound with a rare sesquiterpenoid tropolone skeleton. Its structure was determined by analysis of spectrometric and spectroscopic data, including HRESIMS, 1D, and 2D NMR. The antiproliferative effects of eglerisine were tested in human leukemia lineages. In the Kasumi-1 lineage, an acute myeloid leukemia cell line, eglerisine reduced cell metabolism, as determined by the resazurin assay. Eglerisine did not induce cell death by either apoptotic or necrotic mechanisms. However, a reduction of the absolute number of cells was observed. Eglerisine induced cell cycle arrest after 72 h of treatment by phosphorylation of H2AX histone, reducing the S phase and increasing the G2 phase of the cell cycle.
Keywords: Dulacia egleri; Olacaceae; tropolone sesquiterpene; cell cycle arrest